Analysing Debt Ratio, Equity Ratio, Asset Turnover Impact on Return on Assets in Transport and Logistics - Yonatan Alvin Stefan; Novia Putri Damayanti (Journal of Applied Management and Business, 2025)
This study analyzes the financial performance of transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) during the 2023–2024 period, with a focus on the influence of Debt Ratio, Equity Ratio, then Asset Turnover against Return on Assets. Secondary data were obtained from the company's annual financial reports, processed using robust regression methods, considering the violation of the normality assumption in the data. The results showed that DR and ER had a significant negative effect on ROA, indicating that high proportions of debt and equity can reduce company profitability. This finding is in line with Trade Off Theory, which highlights the financial risks resulting from leverage or excess equity. Meanwhile, ATO was not proven to have a significant effect on ROA, indicating that asset turnover efficiency was not yet able to drive profitability during this study period. The robust regression model was able to explain 32.8% of the variation in ROA, while the remainder was influenced by factors outside the model, such as operational costs, company size, or macroeconomic conditions. This study provides practical implications for management in optimally managing funding structures and improving operational efficiency. For investors, these results provide an important signal in assessing a company's financial risk. Future research is recommended to expand the analysis variables and conduct comparative studies across transportation and logistics sub sectors.